2013
DOI: 10.1016/j.jvs.2012.11.069
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and treatment results of Endurant endograft occlusion

Abstract: At a median follow-up of 1.7 years, Endurant endograft occlusion occurred in 4.0% of 496 patients. Most occlusions occurred ≤ 2 months after EVAR, and rarely after 1 year. A technical justification for occlusion could be found for 60% of patients. A more liberal intraoperative and early postoperative (re)intervention strategy may reduce the occlusion rates and improve outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 39 publications
6
58
0
Order By: Relevance
“…Compared with unilateral limb occlusion, bilateral limb occlusion is relatively uncommon, with a reported incidence ranging from 0% to 0.6% and accounting for 0% to 15% of endograft occlusion cases. 2,3,[6][7][8] Total occlusion of the main body of the bifurcated stent graft is a rare condition and no previous studies have been reported on its detailed therapeutic process.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Compared with unilateral limb occlusion, bilateral limb occlusion is relatively uncommon, with a reported incidence ranging from 0% to 0.6% and accounting for 0% to 15% of endograft occlusion cases. 2,3,[6][7][8] Total occlusion of the main body of the bifurcated stent graft is a rare condition and no previous studies have been reported on its detailed therapeutic process.…”
Section: Resultsmentioning
confidence: 99%
“…Second-or third-generation endografts have been reported to have lower incidences of graft occlusion than firstgeneration endografts. 3,7) Notably, Gore Excluder endoprosthesis (W.L. Gore & Associates, Flagstaff, Arizona), one of the currently available third-generation endografts, has been reported to more suitable for complex iliac anatomy, with a limb occlusion incidence of 0%-1.4%, 4,9) which is lower than that of Zenith stent graft (4.8%-5.5%) 4,6,8) or Endurant endograft (Medtronic Inc, Minneapolis, Minnesota) (3.4%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations